Cytokines and SLPI profiles in children and adults with urinary tract infections - KolesnуkM.; Driianska, V.; Stepanova, N.; Lavrenchuk, O.; Bagdasarova, I.; Poroshina, T.; Holod, V. (Ukrainian Journal of Nephrology and Dialysis, 2019)
Pro- and anti-inflammatory cytokines, SLPI and NGAL are involved in anti-infectious immunity. Studies of these indicators’ role in patients with urinary tract infections (UTIs) may determine their significance as diagnostic and prognostic markers in the case of pyelonephritis and cystitis. The objective of our study was to investigate plasma and urine cytokines and SLPI levels in patients with UTIs, determine the features in children and adults. Materials and methods. ELISA method and related test systems - «Immunotech», «Diaclon» (France); «DRG» (Germany), «Hycult biotechnology» ((Netherlands) were used to study blood cytokine levels in 118 adults and 67 children, SLPI levels in the blood and urine in 59 and 58, respectively. NGAL serum levels of 26 adults with acute pyelonephritis (AP) and 30 adults with chronic pyelonephritis (ChP) were studied using «Human lipocalin-2 / NGAL ELIZA» (Biovendor, Czech Republik) for NGAL. Comparison groups included 10 healthy donors and 11 patients with acute kidney injury (AKI). Results. The study showed an increase in pro- (IL-1, -17, -18, -23, TNF-α, MCP-1) and anti-inflammatory cytokines (IL-17, TGF-β), SLPI, NGAL in patients with UTI, some features in the case of chronic cystitis (ChC), AP and ChP. In adults, TNF-α in the blood and urine, IL-17 in the blood was higher in the case of ChC than ChP. The analysis showed a significant increase in all studied indicators’ levels for AP and ChP in children and adults. The average MCP-1 level in patients with AP was significantly higher than ChP, whereas TNF-α did not differ. In adults, IL-18 and IL-23 were highest in the case of AP, and TGF-β was the highest in the case of ChP. MCP-1, IL-23 levels in the blood of adults were higher than in children in the case of AP, and TNF-α - in the case of ChP. SLPI is involved in the AP pathogenesis and ChP exacerbation. High SLPI levels have been determined in serum and urine (NGAL in the blood) in patients with pyelonephritis (NGAL - AP) who can be used, as well as cytokines, as additional diagnostic and prognostic markers. Conclusions. High levels of TNF-α, MCP-1, and IL-23 in the blood of adults and children confirm their important role in both AP and ChP, but MCP-1 can be considered as an AP predictor/ ChP exacerbation. According to the studied cytokines, adults have a more significant immune response. The SLPI level is an additional feature for diagnosing and monitoring the course of pyelonephritis and cystitis.